Hematological and Morphological Analysis of the Erythropoietic Regenerative Response in Phenylhydrazine-induced Hemolytic Anemia in Mice - Roque, Marta; D´Anna, Cecilia; Gatti, Christian; Veuthey, Tania (Scandinavian Journal of Laboratory Animal Science, 2008)
In this study we developed a mouse model of Phenylhydrazine (PHZ) -induced hemolytic anemia to study erythropoietic regenerative response through clinical, pathological, and morphological studies. Hemolytic anemia was induced in female mice (CF1) using PHZ at a wide range of doses (up to 100 mg/Kg) on days 0 and 2. Hemolytic anemia was observed at 60 mg/kg PHZ on day 4 and was evidenced by decreased HCT (34.3±0.28%), reticulocytosis (51.6±2.10%), anisocytosis, poikilocytosis, leukocytosis, and increased Heinz body count. A time-course and dose-dependence analysis of the regenerative response was performed. HCT decreased on days 2 and 4 in a dose-dependent manner, returning to basal levels on day 8. PHZ only induced reticulocytosis (day 4) at the highest doses tested (60-100 mg/kg). Heinz body formation was dose-dependent. These changes were accompanied by splenomegaly and splenic erythroid hyperplasia. Results revealed that the presence of erythroblastic islands was most clear in the spleen, followed by the liver and kidney. SEM showed Heinz body-containing erythrocytes and spherocyte-like erythrocytes. Anemia recovery results from coordinated action of extramedullary tissues depending on the time post injection and the dose applied. In conclusion, this mouse model allowed us a better understanding of murine erythropoietic regenerative response.